[Rezension von: Kenzo Hiraoka (ed.), Fundamentals of mass spectrometry] - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2014)
Bibliography Fundamentals of mass spectrometryKenzo Hiraoka (Ed.)SpringerISBN: 978-1-4614-7232-2Hardcover, 239 pages2013, €181.89Book’s topicFundamentals of Mass Spectrometry, edited by Kenzo Hiraoka, covers a selection of concepts, methods, and techniques relevant to mass spectrometry, approaching them mostly from a fundamental perspective. In contrast with many application-oriented books and scientific papers, the authors meet the challenge of including and reviewing gas-phase ion chemistry, ion-molecule collisions and reactions, several ionization processes, and excited states.Contents The monograph comprises ten chapters over 248 pages and has 138 high-quality illustrations, 57 of which are in color. Complete bibliographies are provided at the end of each chapter. The book ends with a substantial subject index. The chapters are Collision Theory: Basic Explanation for Collisions in Mass Spectrometry (Chapter 1), Unimolecular Dissociations in Mass Spectrometry (Chapter 2), Fundamental ...